Production and characterization of lipopeptide from Bacillus cereus SNAU01 under solid state fermentation and its potential application as anti-biofilm agent. (January 2016) - Nalini, S.; Parthasarathi, R.; Prabudoss, V.
Abstract: This work was aimed to utilize peanut oil cake as a novel substrate to produce lipopeptide biosurfactant by Bacillus cereus SNAU01 under solid state fermentation (SSF). Central Composite Design (CCD) was performed to optimize the variables for biosurfactant production. The Response Surface Methodology (RSM) results revealed, the optimal conditions for maximal production of biosurfactant were 8.18 g peanut oil cake as substrate, 2.5 ml inoculum level with pH 7 at 30 °C. The biosurfactant was characterized by FT-IR, TLC and GC–MS confirmed the presence of lipopeptide from B. cereus SNAU01. The Confocal Laser Scanning Microscopy (CLSM) proved the effective removal of biofilm by SNAU01 lipopeptide on glass surface. The biofilm disruption of SNAU01 lipopeptide was more efficient at 250 µg/ml against the selected pathogenic strains. The present findings indicated that peanut oil cake as suitable substrate for the production of lipopeptide under SSF by B. cereus SNAU01 and its potential application as anti-biofilm agent.